PEMANFAATAN MEDIA SOSIAL DALAM PENYEBARAN INFORMASI PROGRAM PEMERINTAH (Studi Kasus Sekretariat Daerah Kabupaten Pangandaran) - Evi Novianti; Aat Ruchiyat Nugraha; Lukiati Komalasari; Kokom Komariah; Diah Sri Rejeki (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Social media is one container that is effective in disseminating information. In accordance with the results of research conducted in the Regional Secretariat of Pangandaran Regency that social media is used as a means of communication, discussion and collaboration. Whatsapp groups are created with the aim of sharing information and good discussions with public relations throughout Indonesia, journalists or village heads in the Pangandaran Regency area. Instagram is used to share information about activities carried out in the Pangandaran district secretariat in the community. Youtube is used to disseminate information in audiovisual form. Finally, Facebook is used to explain pictures or videos more fully and specifically. Each social media has advantages and disadvantages, so social media managers who are capable of information technology capabilities are needed.